#TITLE_ALTERNATIVE# - AKBAR HIKMATULOH (NIM : 23408064) ; Pembimbing Prof. Dr. Ir. Abdul Hakim Halim, YUSUP
This study developed a model procurement plan and production plan in the refined sugar industry with a case study in PT. XYZ. The mathematical model was developed using the assumption that demand is only fulfilled from warehouse, raw materials are always available at the supplier and the production is done continuously without any damage to the engine. Decision variable for from the model is ordering lot sizeÃ‚Â’s, ordering decision, the amount of raw material that is sent, inventory of raw materials, the total production, inventory of production. Optimal decision variable is obtained by minimizing total costs. Optimal solution search conducted simultaneously and gradually. Testing and analysis carried out to demonstrate the performance of the model developed models and then compared with the real conditions in the company. Based on model analysis concluded that the procurement raw materials plan and production plans model produces the lowest total cost compared with the real conditions in the company. Sensitivity analysis is conducted to see how changing the model parameters to total cost, and optimal solution. From the sensitivity analysis found that changes in demand, transportation costs, storage costs of raw material and product influence the decision variable values and the total cost significantly.